Is it feasible to pay specialty substance use disorder treatment programs based on patient outcomes?. (1st January 2020) - Hodgkin, Dominic; Garnick, Deborah W.; Horgan, Constance M.; Busch, Alisa B.; Stewart, Maureen T.; Reif, Sharon
Highlights: Some insurers are paying general medical providers based partly on patient outcomes. We reviewed literature on pay-for-outcomes: theory, measures, and application to SUD. There are special challenges in applying pay-for-outcomes to SUD treatment. For SUD treatment it may be necessary to continue paying partly on process measures. Abstract: Background: Some US payers are starting to vary payment to providers depending on patient outcomes, but this approach is rarely used in substance use disorder (SUD) treatment. Purpose: We examine the feasibility of applying a pay-for-outcomes approach to SUD treatment. Methods: We reviewed several relevant literatures: (1) economic theory papers that describe the conditions under which pay-for-outcomes is feasible in principle; (2) description of the key outcomes expected from SUD treatment, and the measures of these outcomes that are available in administrative data systems; and (3) reports on actual experiences of paying SUD treatment providers based on patient outcomes. Results: The economics literature notes that when patient outcomes are strongly influenced by factors beyond provider control and when risk adjustment performs poorly, pay-for-outcomes will increase provider financial risk. This is relevant to SUD treatment. The literature on SUD outcome measurement shows disagreement on whether to include broader outcomes beyond abstinence from substance use. Good measures are available for some of these broader constructs, but the need for risk adjustment still brings many challenges. Results from two past payment experiments in SUD treatment reinforce some of the concerns raised in the more conceptual literature. Conclusion: There are special challenges in applying pay-for-outcomes to SUD treatment, not all of which could be overcome by developing better measures. For SUD treatment it may be necessary to define outcomes more broadly than for general medical care, and to continue conditioning a sizeable portion of payment on process measures.